Isolated Duodenal Crohn's Disease: A Case Report and a Review of the Surgical Management - Faruk Karateke; Ebru Menekşe; Koray Das; Sefa Ozyazici; Pelin Demirtürk (Case Reports in Surgery)
Crohn's disease may affect any segment of the gastrointestinal tract; however, isolated duodenal involvement is rather rare. It still remains a complex clinical entity with a controversial management of the disease. Initially, patients with duodenal Crohn' s disease (DCD) are managed with a combination of antiacid and immunosuppressive therapy. However, medical treatment fails in the majority of DCD patients, and surgical intervention is required in case of complicated disease. Options for surgical management of complicated DCD include bypass, resection, or stricturoplasty procedures. In this paper, we reported a 33-year-old male patient, who was diagnosed with isolated duodenal Crohn’s diseases, and reviewed the surgical options in the literature.